2019
DOI: 10.3390/cancers12010037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Signature of Subtypes of Non-Small-Cell Lung Cancer by Large-Scale Transcriptional Profiling: Identification of Key Modules and Genes by Weighted Gene Co-Expression Network Analysis (WGCNA)

Abstract: Non-small-cell lung cancer (NSCLC) represents a heterogeneous group of malignancies consisting essentially of adenocarcinoma (ADC) and squamous cell carcinoma (SCC). Although the diagnosis and treatment of ADC and SCC have been greatly improved in recent decades, there is still an urgent need to identify accurate transcriptome profile associated with the histological subtypes of NSCLC. The present study aims to identify the key dysregulated pathways and genes involved in the development of lung ADC and SCC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(175 citation statements)
references
References 94 publications
2
166
0
1
Order By: Relevance
“…7 b, c). Previous studies showed that in lung squamous cell carcinoma GNG11 was a novel hub gene in module-related tumor size, and the low mRNA expression of GNG11 was associated with the higher overall survival rate for patients [ 39 , 40 ]. The secretion of PDGFB by gastric carcinoma cells was associated with lymphatic metastasis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 b, c). Previous studies showed that in lung squamous cell carcinoma GNG11 was a novel hub gene in module-related tumor size, and the low mRNA expression of GNG11 was associated with the higher overall survival rate for patients [ 39 , 40 ]. The secretion of PDGFB by gastric carcinoma cells was associated with lymphatic metastasis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is able to cluster highly related genes from microarray samples into different color modules and explore the relationship between the genes and cancer traits [20]. WGCNA has already been used in various oncological studies to explore hub genes and the regulatory relationships between them [21][22][23]. In our study, we preformed WGCNA to select highly related module genes, which helped us elucidate the more meaningful RNAs for further prediction.…”
Section: Discussionmentioning
confidence: 99%
“…WGCNA was conducted by adopting the R packages of "wgcna," matrixStats," dynamic tree cut," fast cluster," Hmisc" in R software [10]. Pearson's correlation matrices were prepared for all pair-wise genes.…”
Section: Wgcna Constructionmentioning
confidence: 99%